PENGEMBANGAN E-MODUL BERBASIS EDUCATION FOR SUSTAINABLE DEVELOPMENT UNTUK KELAS IV SEKOLAH DASAR - Nunu Fuji Syafitri; Ghullam Hamdu (JURNAL PENDIDIKAN DASAR, 2023)
Abstract: This research is a development study that intends to produce a product of the electronic teaching module with Education for Sustainbale Development Based for primary school students. Data collection techniques used by observation, interview, and focus group discussion (FGD). Electronic modes have been validated by media and design experts, materials experts, and pedagogic experts. They have been tested on students. Research shows the feasibility of the e-modules from the experts’ validation. The result had given by media and design expert is 3.89, by material expert is 3.70, and pedagogists expert is 3.48. They are in excellent category. E-module worthiness assessment results based on student responses are 3.66 from the Maximal score, is 4. This proves that the e-modules are worthy of being used as a self-sufficient teaching supplement for students. Keywords: Development; E-Modul; Education for Sustinable Development  Abstrak: Penelitian ini merupakan penelitian pengembangan yang bertujuan untuk menghasilkan produk berupa bahan ajar elektronik modul berbasis Education for Sustainbale Development untuk siswa kelas IV Sekolah Dasar. Teknik pengumpulan data yang digunakan observasi, wawancara dan Focus Group Discussion (FGD). Elektronik modul ini sudah divalidasi oleh ahli media dan desain, ahli materi, dan ahli pedagogic dan sudah diuji coba kepada siswa. Hasil penelitian menunjukan kelayakan e-modul dari hasil validasi para ahli, yaitu ahli media dan desain sebesar 3,89, ahli materi sebesar 3,70, dan ahli pedagogik sebesar 3,48 dengan kategori sangat baik. Hasil penilaian kelayakan e-modul berdasarkan respon siswa sebesar 3,66 dari skor maksimal 4. Hal ini membuktikan bahwa e-modul layak digunakan sebagai suplemen bahan ajar mandiri bagi siswa. Kata Kunci: Pengembangan; E-Modul; Education for Sustinable Development